Hardware Implementation of Intrusion Detection System for Ad-Hoc Network - Reji Mano; P.C. Kishore Raja; Christeena Joseph; Radhika Baskar (International Journal of Reconfigurable and Embedded Systems (IJRES), 2016)
New technologies have been developed in wireless adhoc network need more security. To widespread the adhoc networks we turn in the attention of wireless hand held device mobile phones communicate with short distance using wireless lan card or Bluetooth. The performance of mobile phone are improved greatly for last few years .so security is more important for mobile networks In this paper  hardware implementation of single hop ad-hoc network is implemented and analysed using microcontroller. The protocol implemented in this paper is primarily based on, Ad hoc On-Demand Distance Vector routing. We adopt On Demand Distance Vector routing solely based on source routing and “On Demand” process, so each packet does not have to transmit any periodic routing information. We implemented   intrusion detection system with five different nodes and the performance parameters like packet delivery ratio, throughput, delay are computed with attacker and without attacker and on demand distance vector routing protocols is proposed to implement in hardware using Zigbee